A Comparative Stylistic and Technical Analysis of Four Ancient Egyptian Bronzes from Ditsong Museum, South Africa : General Articles - Harcombe, Mariette (Journal for Semitics, 2023)
The Ditsong National Museum of Cultural History in Pretoria, South Africa, is a holding institute for thousands of objects that are accessioned in its collections, including a small collection of Egyptian antiquities. As a multitude of these objects have been donated to the museum over many decades by private collectors, some information regarding object provenance and provenience is unknown. Missing details often include the object’s place of origin, its relative production date, production materials, as well as production methods and techniques. The archaeology collection features a small collection of ancient Egyptian bronze statuettes, also known as votive figures. Four bronzes, Sekhmet, Bastet/Cat, the Jackal/Dog, and the ibis, were investigated as part of the author’s doctoral study, which employed a mixed methodological approach that combined surface investigations, tomography, and comparative stylistic analysis to provide insights into ancient production. This article focuses on a comparative stylistic analysis in which online museum collections were consulted alongside published descriptions of similar objects and the gods/goddesses they depict. Following the analysis, recommendations are made towards the re-identification of two of the figures, while additional insights gained about their possible function could be incorporated into the Museum’s object catalogue.